Rethinking Port Role as Transport Corridor under Symbiosis Theory-Case Study of China-Europe Trade Transportation - Tao, Kan; Chao, Yiying (International Journal of Sustainable Development & World Policy, 2019)
As a modern port, its roles have been endowed with many new functions. Extant literatures in transportation industry view port as an individual economic entity to improve its competition or evaluate its performance. By focusing on port original concept as node in transportation, its critical role as providing service to related industry shouldn't be largely change or forget. Under this perspective, port is not as commercial organization, is transport corridor to contribute to public welfare. Hence, creating synergistic effects in a research system which can be regard as symbiotic. Our case study on the China-Railway Express (CR Express) hub-port construction in the background of China-Europe trade transportation address research question as how to construct China-Europe transport corridor. In order to achieve a complete and comprehensive understanding of the under-explored topic, we use a mixed methods, including semi-structured interview and establish symbiotic model as symbiotic transport capacity growth model and clock model. Generally, we conclude that trade and each transportation pattern can be regard as a symbiotic system and more importantly, port as public infrastructure, its service providing and transport corridor are significant contribute to the symbiotic system. Contributions and managerial implications are provided at the final section of our research which not only have guidance value on China, but also the ports whose located country is one of ‘One Belt and One Road’ countries.